Detecting Solar Flare Precursors Using DEFT - Larisza D. Krista (The Astrophysical Journal, 2024)
The Detection and EUV Flare Tracking (DEFT) tool automatically identifies flare precursors in extreme ultraviolet (EUV) observations in a fast and consistent manner, with minimal computational overhead. DEFT currently uses GOES/SUVI 304 Å observations to detect, group, and flag sudden impulses that could be precursors to flares. In this study, we analyzed precursor signatures before 351 flares (150 C, 150 M, and 51 X class flares) that occurred from 2017 to date. Across these magnitudes, precursors were detected for 93% of the flares when using a 6 hr window before the flare start times. Using superposed epoch analysis, we found that elevated precursor activity tends to occur across all magnitude flares in the last 2 hr before the flares. The frequency of precursors gradually increases before M class flares but decreases for C class flares. We also found that in the last 20 minutes there is a significantly higher precursor frequency, pixel count, and power associated with M class flares than C class flares. We suggest that the observed EUV precursors are the observable signatures of small-scale magnetic reconnection events, and the consistently increasing frequency of precursor activity could indicate that the region is becoming increasingly unstable and reaching a critical stage that could result in flare initiation. Continuing research on EUV precursors is essential to better understand preflare processes that build and reduce magnetic instability prior to main-stage flares. The consistent and reliable detection and differentiation of EUV precursors could also complement and significantly improve current flare forecasting efforts.